Gaussian estimation of single-factor continuous-time models of the South African short-term interest rate - Aling, Peter (School of Economics, 2024)
This paper presents the results of Gaussian estimation of the South African short-term interest rate. It uses the same Gaussian estimation techniques employed by Nowman (1997) to estimate the South African short-term interest rate using South afrcan Treasury bill data. A range of single-factor continuous-time models of the short-term interest rate are estimated using a discrete-time model and compared to a discrete approximation used by Chan, Karolyi, Lonstaff and Sanders (1992a). We find that the process followed by the South African short-term interest rate is best explained by the Constant Elasticity of Variance (CEV) model and that the conditional volatility depends to some extent on the level of the interest rate. In addition we find evidence of a structural break in the mid- 1980s, confirming our suspicions that the financial liberalisation of that period affected the short rate process.